Nanoribbons or weakly connected acenes? The influence of pyrene insertion on linearly extended ring systems. Issue 47 (25th November 2021) - Ai, Qianxiang; Smith, Tanner; Liyanage, A. D. Thilanga; Mazza, Samuel M.; Parkin, Sean R.; Anthony, John E.; Risko, Chad
Abstract : Pyrene moieties inserted among acene units do not result in long acene-like structures; rather the pyrene-inserted acene structure is, electronically, a series of (nearly) isolated acenes. Abstract : Derived from the lateral fusion of benzene rings, acenes are a class of π-conjugated molecules containing a single aromatic sextet, where system size is inversely correlated with chemical stability. In the pursuit of creating graphene nanoribbons/nanowires, several extended-ring structures have been synthesized through linear combinations of azaacenes and pyrene. Importantly, these extended systems demonstrate enhanced chemical stability and allow for the construction of macromolecular-sized structures. Here, we present a combined quantum-chemical and experimental study to reveal the cost of these improved characteristics in fully carbon-based systems. The results clearly show that pyrene moieties inserted among acene units do not result in long acene-like structures, rather the pyrene-inserted acene is, electronically, a series of (nearly) isolated acenes. The origin of pyrene's electronic blocking effect and implications on oxidized and photoexcited states of these extended-ring systems are detailed. The results of this investigation definitively show that coupling pyrene in an orthogonal orientation (through the 4, 5/9, 10 positions or e/l faces) to acenes should be eschewed if nanographene-/nanowire-like structures are desired.